The Concept of Terrorism in Indonesia and Malaysia - Imam Syafei; Marwan (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of analyzing the concept of terrorism in Indonesia and Malaysia. This study is a normative legal study, to determine the differences and similarities between the legal systems of one country and another. Comparison of Indonesia and Malaysia. Application of the Concept of Terrorism in Positive Law Indonesia as we know that the Criminal Code (KUHP) has not specifically regulated and is not adequate enough to eradicate Criminal Acts of Terrorism, the Indonesian Government feels the need to form a Law on the Eradication of Criminal Acts of Terrorism, namely by compiling a Government Regulation in Lieu of Law (Perpu) number 1 of 2002, which on April 4, 2003 was ratified into Law number 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism. Finally, with the issuance of Law Number 9 of 2013 concerning the Prevention and Eradication of Criminal Acts of Terrorism Funding, Indonesia positions itself as a country that participates internationally in efforts to eradicate terrorism funding. Meanwhile, the Implementation of the Concept of Terrorism in Malaysian Law is contained in the Internal Security Act of Malaysia or the Domestic Security Act, which is an act created by the Malaysian Parliament that applies in West Malaysia and East Malaysia. The Domestic Security Act of 1960 (Act 82), better known as the ISA, aims to prevent threatening actions by a substantial group of people, both from within and outside Malaysia. The definition of a terrorist contained in the Preliminary Internal Security Act of Malaysia, Interpretation section, refers more to individuals who are personally involved in acts of terrorism. The definition of a terrorist in the ISA is preferred because acts of terrorism can be carried out by individuals, groups of people or countries as an alternative to openly declaring war. Then, from that definition, further steps can be taken in an effort to protect domestic security, public order and eradicate terrorism, this is the basis for the TNI to be involved.